Urine Phthalate Levels and Liver Function in US Adolescents: Analyses of NHANES 2007–2016 - Xiang, Shiting; Dong, Jie; Li, Xun; Li, Chao (Frontiers in Public Health, 2022)
Background: Phthalates are non-persistent chemicals with endocrine-disrupting abilities widely used in a variety of consumer products. Evidence for the effects of phthalate exposure on liver function in adolescents is lacking. Methods: Data were analyzed from the combined 2007-2016 National Health and Nutrition Examination Survey (NHANES). Ultimately, a total of 1650 adolescents aged 12-19 years were selected as the samples. Weighted linear regression was used to investigate the effects of urinary phthalate metabolites on liver function indexes. Results: Weighted Linear regression models showed that MCOP was negatively associated with TBIL (β=-0.0435, P FDR = 0.007), ΣDEHP (β = -0.0453, P FDR = 0.003) and MCOP (β = -0.0379, P FDR = 0.006) were negatively correlated with ALB, while MCPP was positively correlated with ALB (β = 0.0339, P FDR = 0.024), and MCOP was negatively correlated with TP (β =-0.0551; P FDR = 0.004). Conclusions: Phthalate metabolites were significantly but weakly associated with changes in liver function indicators among US adolescents. Future work should further examine these relationships.